Georgia Architectural and Historic Properties Survey of Labelle Ave. [6], Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Labelle Ave. [6], Sycamore, Turner County, Ga., 1981. Double pen, possibly saddlebag, plan. Three rooms plus shed addition. Tin gabled roof, with brackets. Shed porch supported by square posts. Clapboard siding. Double sash windows with 6/6 lights. Interior chimney removed, suggesting possible saddlebag. On concrete block foundation. Fair condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Labelle Ave. [6], Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 53.2 MB (55,826,646 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)